Non-state armed groups in the Myanmar peace process: What are the future options? - Helene Maria Kyed; Mikael Gravers (Danish Institute for International Studies (DIIS), 2014)
In Myanmar/Burma the government and the many ethnic non-state armed groups (NSAGs) are close to signing a national ceasefire agreement that will end almost 65 years of conflict in the country's resource-rich borderlands. This is taking place alongside a transition from totalitarian military rule towards democracy, and a rapid influx of international aid agencies and foreign investors. While there is progress in the peace negotiations, the process has been contested and fighting has continued in Kachin state. A key controversy concerns the future status of the many NSAGs that represent different ethnic nationalities, such as the Karen and the Mon. The NSAG leaders demand a political settlement that allows them to retain arms and political positions within a federalist system. The government has now agreed to discuss a federal system, but this is not backed by the powerful Burmese army generals. Moreover, the term 'federalism' can have many meanings. Left out of the peace negotiation talks has been any open discussion of what will happen to the many middleand lower-ranked armed actors after an agreement has been reached. Failure to include this may be detrimental to sustainable peace and to the building of trust in the peace settlement. This paper is a preliminary attempt to discuss the future options for the members of the ethnic NSAGs in Myanmar: what 'exit' options do the NSAG members have after decades of conflict and, for many of them, entire lives spent inside the armed groups? How do they envision their future - as armed actors, civil servants, politicians, businessmen or something else? In addressing these questions we draw on interviews held in Mon and Karen states in January 2014 and on prior research. We engage with that segment of the international peacebuilding literature which debates the transformation of ex-combatants through different forms of `Demobilization, Disarmament and Reintegration' (DDR) programmes. A core argument of the paper is that in the Myanmar context it is highly unlikely that conventional DDR programmes will suffice to support sustainable peace and stability. This is not only due to the exceptionally low involvement of international aid agencies in the peace process, but also because of the predominant focus in DDR programmes on disarmament and on economic incentives to successful integration. In Myanmar this overlooks key political motives behind both the causes of conflict and the negotiations for peace. It also ignores the fact that the NSAGs have enjoyed decades of state-like control over territories and people. Based on this, we do not take a point of departure in disarmament, but instead outline seven different integration options. These consist of a combination of different forms of political, economic, civil society and security sector integration. We call for more in-depth analyses of the armed groups in Myanmar as a complex and dynamic set of actors with various motives, aspirations and incentives. Finally, the paper concludes by reflecting on the future role of international aid agencies in the context of the peace process.
Keywords: 300